BPS Wilson loop in N=2 superconformal SU(N) "orientifold" gauge theory and weak-strong coupling interpolation - Beccaria,M; Dunne,G; Tseytlin,AA (The Journal of High Energy Physics, 2021)
We consider the expectation value W of the circular BPS Wilson loop in N = 2 superconformal SU(N) gauge theory containing a vector multiplet coupled to two hypermultiplets in rank-2 symmetric and antisymmetric representations. This theory admits a regular large N expansion, is planar-equivalent to N = 4 SYM theory and is expected to be dual to a certain orbifold/orientifold projection of AdS5 × S5 superstring theory. On the string theory side W is represented by the path integral expanded near the same AdS2 minimal surface as in the maximally supersymmetric case. Following the string theory argument in [5], we suggest that as in the N = 4 SYM case and in the N = 2 SU(N) × SU(N) superconformal quiver theory discussed in [19], the coefficient of the leading non-planar 1/N2 correction in W should have the universal λ3/2 scaling at large ’t Hooft coupling. We confirm this prediction by starting with the localization matrix model representation for W. We complement the analytic derivation of the λ3/2 scaling by a numerical high-precision resummation and extrapolation of the weak-coupling expansion using conformal mapping improved Padé analysis.